Work Engagement as a Moderator of Workload and Internal Mobility on Employee Performance - Gandy Novanda Pratama; Nurhidayati Nurhidayati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines how Workload and Internal Mobility shape Employee Performance, with Work Engagement as a moderating variable, among staff at the Tanjung Emas Customs and Excise Service Office, Indonesia. Despite staffing deficits from 2023 to 2025, the office’s Organizational Performance Score reached an “Exceptional” 117.04%, while Customs Clearance Time simultaneously deteriorated, an operational paradox motivating this inquiry. Grounded in Job Demands-Resources (JD-R) Theory, a quantitative cross-sectional design was employed. Data from 118 active employees, selected via purposive sampling, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Full Collinearity Assessment confirmed that common method bias was not a serious threat, with all structural path VIF values between 1.011 and 1.167, well within the 3.30 threshold. All four hypotheses were supported. Workload exerted a significant negative effect on Employee Performance (β = −0.374, p < .001), while Internal Mobility produced a strong positive effect (β = 0.406, p < .001). Work Engagement significantly moderated both relationships, attenuating the negative impact of Workload and amplifying the positive impact of Internal Mobility. An independent-samples t-test further revealed that employees in split-location arrangements (n = 35, 29.7%) reported markedly lower engagement (M = 2.58 vs. 3.25; t = −5.21, p < .001; d = 1.05), a pattern attributed to what this study terms “geographic dislocation demand” , the cumulative psychological burden of sustaining a residential separation between one’s posting location and one’s family. Practical implications include workload automation, structured peer-support for rotated employees, and affirmative welfare policies for geographically displaced staff.